Síntesis de tetrahidrocromenos y pirazol [3, 4-b] - 4h - piranos substituidos a partir de aldehidos aromáticos, compuestos 1, 3 - dicarbonílicos y 1 - fenil - 3 - metil - 2 - pirazolin - 5 - ona. - Rodríguez Guzmán, Miltón César (2013)
This research work deals with the synthesis of substituted tetrahydrochromenes and pyrazolo[3,4-b]-4H-pyrenesby the dehydration of the adducts formed by the tandem Knoevenagel–Michael reaction of aromatic aldehydes with 1,3-dicarbonílic compounds and analogous as 1-fenil-3-metil-2- pirazolin-5-ona,benzaldehyde derivatives and active methylene compounds as dimedone, ethyl cyanoacetate and ethyl acetoacetate interact by a Knoevenagel reaction in ethanolusing piperidine as catalyst to produce ethylenic derivatives. In the Michael addition, the ethylenic derivatives react with 1-fenil-3-metil-2- pirazolin-5-ona, to produce intermediate adducts that by dehydration, in the presence of hydrochloricacid, yield the final products. The reaction was monitored by thin layer chromatography (TLC). Tetrahydrochromenes and pyrazolo[3,4-b]-4H-pyranes were obtained in acceptable yields (35-78%),with melting points between 118 and 290°C and Rf values between 0.46 and 0.88.The intermediate and final products structures were verified by infrared spectroscopy.